The Analysis of Consumers’ Purchasing Factors on Boga Service Start-Up - Finolda, Finolda; Padmalia, Metta (Jurnal Entrepreneur dan Entrepreneurship, 2019)
This study aims to analyze the factors of consumer behavior in purchasing Empal Catering Bibik. The factors examined in this study are cultural factors, social factors, personal factors and psychological factors. The population in this study were consumers of Empal Catering Bibik. The sample size of 40 respondents. The research samples were collected using non-probability sampling methods and purposive sampling techniques. The research data was taken by using questionnaires which were distributed to respondents. Data analysis using the second order confirmatory analysis factor analysis. The results of data processing shows that consumer behavior factors in purchasing consumer food service start-ups are personal factors and psychological factors.